Implementation of a logistic map to calculate the bits required for digital image steganography using the least significant bit (LSB) method - Al Maki, Wikky Fawwaz; Muktyas, Indra Bayu; Arifin, Samsul; Suwarno, .; Mohd Khairul Bazli, Mohd Aziz (Science Publications, 2023)
The LSB method in steganography usually only uses the last bit or the last few bits that are the same for all pixels. This is very easy to solve by using a bitwise shift left operation so that the last bit becomes the leading bit (MSB). Some techniques combine steganography and cryptography through two different processes. In this study, a new technique is proposed to perform steganography and cryptography together. The random sequence obtained from the logistic map is used to determine the number of bits in the LSB method. Furthermore, testing was carried out on several grayscale images. The result obtained is that the hidden images cannot be opened easily. The level of sensitivity is very small, reaching 10-15.